A 4-year review of surgical and oncological outcomes of endoscopic endonasal transpterygoid nasopharyngectomy in salvaging locally recurrent nasopharyngeal carcinoma - Tang, Ing Ping; Ngui, Ling Xiu; Ramachandran, Komathi; Lim, Li Yun; Voon, Pei Jye; Yu, Kong Leong; Narayanan, Prepageran; Carrau, Ricardo (Springer, 2019)
Purpose: To study the surgical and oncological outcomes of endoscopic endonasal transpterygoid nasopharyngectomy (EETN) in salvaging locally recurrent nasopharyngeal carcinoma (NPC). Method: This was a retrospective clinical record review study carried out at a tertiary centre from June 2013 until May 2017. A total of 55 locally recurrent NPC patients (rT1–rT4) underwent EETN performed by single skull base surgeon with curative intention with postoperative adjuvant chemotherapy but without postoperative radiotherapy. Results: There were 44 (80.0%) males and 11 (20.0%) females, with mean age of 52.5 years. The mean operating time was 180 min (range 150–280 min). 85% (47/55) of patients achieved en bloc tumour resection. 93% (51/55) of patients obtained negative microscopic margin based on postoperative histopathological evaluation. Intraoperatively, one (1.8%) patient had internal carotid artery injury which was successfully stented and had recovered fully without neurological deficit. There were no major postoperative complications reported. During a mean follow-up period of 18-month (range 12–48 months) postsurgery, five patients (9.1%) had residual or recurrence at the primary site. All five patients underwent re-surgery. One patient at rT3 passed away 6 months after re-surgery due to distant metastasis complicated with septicaemia. The 1-year local disease-free rate was 93% and the 1-year overall survival rate was 98%. Conclusions: EETN is emerging treatment options for locally recurrent NPC, with relatively low morbidity and encouraging short-term outcome. Long-term outcome is yet to be determined with longer follow-up and bigger cohort study. However, a successful surgical outcome required a very experienced team and highly specialised equipment. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.